Evaluasi desain kursi kuliah menggunakan Metode User Experience Questionnaire (UEQ) - Gunanda Tiara Maharany; Rizqie Anandita Zafs; Laura Lam Ulina Br Panggabean (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2026)
Lecture chair design plays an important role in creating a comfortable and productive learning environment. However, chair evaluations generally still focus on physical aspects, while user experience receives less attention. This study aims to evaluate lecture chair design using the User Experience Questionnaire (UEQ) method to understand the influence of changing user behavior and the need for learning devices such as laptops or tablets on chair design. These changes create new demands for the comfort and functionality of lecture chairs in modern education. The research methods include surveys and direct observations in classroom environments. The respondents consisted of 100 design students, both male and female, belonging to Generation Z. The collected data were analyzed using the UEQ method to measure user satisfaction with the current chair design. Therefore, this study is expected to identify chair performance based on the user experience of Generation Z students.